APPLICATIONS FOR ARTIFICIAL INTELLIGENCE AND ITS IMPACT ON REDUCING THE RISK OF HIDDEN ACCOUNTING-A FIELD STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES OF AUDIT FIRMS AND IRAQI COMPANIES REGISTERED IN THE IRAQ STOCK EXCHANGE FOR THE PERIOD FROM 2024 2025 (World Economics and Finance Bulletin, 2025)
THE RESEARCH
Keywords: Artificial intelligence applications